2022
DOI: 10.3389/fphar.2022.932205
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the pathogenesis of diabetic kidney disease by microarray data analysis

Abstract: Diabetic kidney disease (DKD) is a major complication of diabetes mellitus, and the leading contributor of end-stage renal disease. Hence, insights into the molecular pathogenesis of DKD are urgently needed. The purpose of this article is to reveal the molecular mechanisms underlying the pathogenesis of DKD. The microarray datasets of GSE30528 and GSE30529 were downloaded from the NCBI Gene Expression Omnibus (GEO) database to identify the common differentially expressed genes (DEGs) between the glomerular DKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…A DEG analysis revealed that more than half of the genes (∼15k) were significantly differentially expressed (p < 0.05; Student’s t-test with Benjamini-Hochberg correction [29]). This uncommonly high number of DEGs, which is typically on the order of a few hundred in studies of blood samples from patients with other diseases, such as coronary artery disease [30], obesity [31, 32], diabetes [33, 34] or kidney [35], led us to hypothesize that the observed variability might arise from cellular heterogeneity across synovial biopsies, rather than from intra-cellular gene expression differences between the two tested groups. To test this hypothesis, we used xCell [36] to estimate the relative proportions of the various cell populations present in our samples.…”
Section: Resultsmentioning
confidence: 99%
“…A DEG analysis revealed that more than half of the genes (∼15k) were significantly differentially expressed (p < 0.05; Student’s t-test with Benjamini-Hochberg correction [29]). This uncommonly high number of DEGs, which is typically on the order of a few hundred in studies of blood samples from patients with other diseases, such as coronary artery disease [30], obesity [31, 32], diabetes [33, 34] or kidney [35], led us to hypothesize that the observed variability might arise from cellular heterogeneity across synovial biopsies, rather than from intra-cellular gene expression differences between the two tested groups. To test this hypothesis, we used xCell [36] to estimate the relative proportions of the various cell populations present in our samples.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has revealed that albuminuria can activate the Wnt/β-catenin signaling pathway in renal TECs, promoting the expression of TLR4/NLRP3-associated chemokines and inflammatory factors, thereby causing renal tubular and tubulointerstitial inflammation ( 57 ). Microarray data analysis has revealed the important role of inflammation-related signaling pathways in the pathogenesis of both glomerular and tubular DKD ( 58 ). The TECs of patients with DKD are affected by the inflammatory response, resulting in excessive production of intracellular inflammatory mediators which further activate apoptosis, glycolysis, and apoptosis-related pathways and induce renal tubular injury.…”
Section: Mechanismmentioning
confidence: 99%
“…In the past, renal impairment due to diabetes mellitus was predominantly a condition that was first preceded by albuminuria and then followed by a decrease in eGFR ( 1 , 2 ). Recently, however, a decrease in glomerular filtration rate (GFR) without obvious albuminuria has been observed.…”
mentioning
confidence: 99%
“…Recently, however, a decrease in glomerular filtration rate (GFR) without obvious albuminuria has been observed. Therefore, the concept of diabetic kidney disease has been proposed as an umbrella concept for diabetic nephropathy ( 1 , 2 ). In recent years, improvements in renal prognosis with SGLT2 inhibitors and GLP-1 receptor agonists have been reported, and the effects of these drugs are actually felt in clinical practice ( 3 ), but the pathogenesis of DKD still remains largely unexplored.…”
mentioning
confidence: 99%
See 1 more Smart Citation